Improving paraffin precipitate inhibition using glycine and Palm-based Methyl Ester Sulfonate (MES) eco-friendly inhibitors. - Nazliah Binti Surpina; Mysara Eissa Mohyaldinn; Abdullah Abduljabbar; Mohammed Abdalla Ayoub (PLoS ONE)
Oil fields located in cold environments and deep-sea locations often face challenges with paraffin wax buildup in pipelines during long-distance crude oil transportation. Various strategies have been employed to address this issue, with chemical methods being the most effective and economical. However, traditional chemical inhibitors present problems due to their high toxicity and low biodegradability, leading to increased operational costs and environmental concerns. This study focuses on developing an eco-friendly paraffin inhibitor system using three different concentrations of Glycine and Palm-based Methyl Ester Sulfonate (MES). Experiments were conducted on crude oil samples from the Dulang Oilfield. The experimental measurements include wax appearance temperature (WAT), pour point temperature (PPT), and rheological tests in the absence and presence of the proposed inhibitors. The results revealed that both Glycine and MES can effectively reduce WAT, viscosity, and yield point. Specifically, 10% Glycine was the best inhibitor, reducing WAT by 23.3%. However, MES (1%, 5%, and 10%) demonstrated greater overall effectiveness, with an average WAT reduction of 13.76% compared to Glycine's 10.85%. MES also shows a better performance in reducing viscosity and yield stress. While PPT results were insignificant, MES is recommended as a flow improver rather than a pour point depressant. The successful development of these newly formulated chemical inhibitors promises an environmentally sustainable and economically efficient approach to maximizing oil production from mature fields while mitigating paraffin precipitation.